Management of European floodplain grasslands for plant biodiversity - Christopher B. Joyce (1998)
European floodplain grasslands are characterized by periodic flooding and regular management, usually cutting and grazing as part of an agricultural system. Past losses and ecological degradation have been due largely to river regulation and either agricultural intensification or abandonment and have resulted in a substantial reduction in area across Europe. Nevertheless, the remaining resource supports considerable biodiversity and a high level of biological production. A better quantitative understanding of the functioning of these grasslands is required in order to establish effective conservation management within a sustainable land use system. The thesis examines the impact of key management factors on three important functional characteristics of the biodiversity of floodplain plant communities, namely plant diversity (measured by species diversity), cover (%) and primary production (above-ground biomass), on two floodplain grasslands of the River Trent, UK and a third on the the Luznice river, the Czech Republic. Field investigations of the effects of cutting, grazing, cessation of management, the influence of floodborne litter, and the impact of fertilizer nitrogen were undertaken over periods of between one and three seasons. These demonstrated that floodplain grassland plant communities are sensitive to variations in management and that impacts on communities are mediated particularly through effects on plant competition. Productive competitive species were encouraged both by abandonment and fertilizer application whereas cutting and grazing management, and the imposition of litter, favoured stress-tolerating perennials. Species diversity decreased both with high inputs of litter and additions of fertilizer. Plant community responses and competitive strategies of key species are discussed in the context of biodiversity conservation, ecological restoration and management of European floodplain grasslands.